Les islamistes à l’épreuve du printemps arabe et des urnes : une perspective critique - Haoues Seniguer (L’Année du Maghreb)
The Arab world’s social revolts that began in Tunisia in December 2010 were a clear indicator not only of the socio-economic frustrations and democratic expectations of Arab peoples, most of whom were in favor of the fall of authoritarian regimes, but also of ambivalent, even contradictory positions in political Islamist movements vis-à-vis these regimes. Although Islamist movements or parties neither initiated nor joined collective mobilizations right away, their restraint revealed two new aspects : on the one hand, contrary to what certain literature about Islamists may have theorized, the repression that had most often affected them had not deprived them permanently of engaging in collusive transactions with authoritarian regimes, whose longevity they even had ended up accepting and getting accustomed to. That is why, during the early days of revolt, they carefully reflected upon the possible drawbacks of a premature commitment to the protesters and sometimes refused to join them, as did Morocco’s Party of Justice and Development (PJD), at least as a collective player ; on the other hand, these social uprisings brought to light the existence of rifts within Islamist movements, both between the leaders and the base in each of the two groups respectively, and between the “older” and the “younger” generations. Finally, these social uprisings showed, in a number of countries such as Morocco, that legalistic Islamists may well play the game of authoritarianism and share in a form of obsession of social control of the population, as well as preservation of moral order. That did not stop them from winning elections in Morocco, Tunisia and Egypt, not only because of the patently discredited political class in general, but also, more specifically, through their social networks and a form of campaign against corruption and moralization of public life.